Students’ Motivation in Learning English at MTs Cendekia Muhammadiyah Kotamobagu - Wahyu Wijayati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Motivation is one of the most important aspects of the learning process. Without motivation, learning objectives are difficult to achieve. When students possess motivation in the learning process, they will better understand the material, especially English. The purpose of this study is to determine the students’ motivation in learning English among seventh-grade students at MTs Cendekia Muhammadiyah Kotamobagu. This research employed a descriptive qualitative method. The data were collected through a student motivation questionnaire consisting of ten items and an interview containing five questions. The data were analyzed using percentages and descriptive explanations. The main findings show that the students are generally highly motivated. Based on the results of the questionnaire and interviews, it can be concluded that the seventh-grade students at MTs Cendekia Muhammadiyah Kotamobagu possess strong motivation in learning English. The questionnaire results revealed that most students agreed with the positive statements, indicating their enjoyment in learning English. Furthermore, the interview results show that students are highly interested in learning English. However, teachers should be more creative in using media, strategies, or materials in the teaching and learning process to further enhance students’ motivation.